2003
DOI: 10.1108/eb060896
|View full text |Cite
|
Sign up to set email alerts
|

Model for Predicting Architect's Performance in Building Delivery Process

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Traditionally, all the professionals that constitute the project team (architects, civil, structural, mechanical and electrical engineers and quantity surveyors) perform both task functional and managerial important roles irrespective of the management approach adopted in the delivery of the construction projects and the roles are crucial towards the attainment of the project goals. Oyedele et al (2003) empirically attested that, PM practice has become an integral part of architecture practice in most developing countries. Inspite of this observation and development affirmed by Oyedele et al (2003), it can be attested that, practically, PM penetration in the construction industry in respect of architectural consulting practice at the infantry stage.…”
Section: The Case Of the Architects' Pm Competencies And Performance mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, all the professionals that constitute the project team (architects, civil, structural, mechanical and electrical engineers and quantity surveyors) perform both task functional and managerial important roles irrespective of the management approach adopted in the delivery of the construction projects and the roles are crucial towards the attainment of the project goals. Oyedele et al (2003) empirically attested that, PM practice has become an integral part of architecture practice in most developing countries. Inspite of this observation and development affirmed by Oyedele et al (2003), it can be attested that, practically, PM penetration in the construction industry in respect of architectural consulting practice at the infantry stage.…”
Section: The Case Of the Architects' Pm Competencies And Performance mentioning
confidence: 99%
“…Oyedele et al (2003) empirically attested that, PM practice has become an integral part of architecture practice in most developing countries. Inspite of this observation and development affirmed by Oyedele et al (2003), it can be attested that, practically, PM penetration in the construction industry in respect of architectural consulting practice at the infantry stage. Against this, demonstrating some level of PM skills is critical to the success of architects in deliverying high tasks performance in project delivery across all the project life cycle phases (Odusami, 2002).…”
Section: The Case Of the Architects' Pm Competencies And Performance mentioning
confidence: 99%
“…The generic assessment of the critical PM competencies of architects (see Table 3) reveals both expected and unexpected results. The emergence of 'Effective cost control and financial resource management skills', 'Efficient communication with all project participants and stakeholders', 'Effective in managing different persons À client, main and sub-contractors À and expectations' and 'Personal and project time management skills' seems to support studies by Dogbegah et al (2011) and converge with the comparative assessments in the body of literature on factors influencing team performance and role effectiveness (Ling 2002;Oyedele et al 2003;Ogunsemi et al 2008;Dogbegah et al 2011). According to Dogbegah et al (2011), skill in management of financial resources remains among the key competencies required of all project professionals in the Ghanaian construction industry.…”
Section: Discussionmentioning
confidence: 83%
“…Ling (2002) and Oyedele et al (2003) revealed that architects are gaining employment in organizations and the construction industry beyond their traditional roles. Fadamiro and Ogunsemi (1996), Odusami and Iyagba (2001) and Lampel (2001) agreed that architects are most suitable for project leadership, based on their knowledge and skills in the relevant fields of managing and delivering construction projects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation